Askara yang Diiringi Kegelapan: Paradoks Etika Lingkungan Hidup Pada Kawasan Ekowisata - Risnawati; Hamid, Ismar (Huma: Jurnal Sosiologi, 2024)
The development of ecotourism activities presents various characteristics of the behavior of tourists and the surrounding community which have implications for the preservation of nature. This study aims to describe environmental ethics in the community, tourists and the management of ecotourism in Bukit Tahura Sultan Adam. The research method used is qualitative, with the type of case study research. Data collection used observation instruments, in-depth interviews and documentation. The results showed that in the ecotourism area of Bukit Tahura Sultan Adam, anthropocentrism behavior was very clear. In accordance with the review of how humans see nature, this behavior is classified into 2 (two) forms of anthropocentrism. First, absolute anthropocentrism which assesses nature only as a source of life that is utilized for human needs. This ethic is represented by the attitude of people who only focus on protecting natural objects that are considered to provide direct benefits to humans. Second, moderate anthropocentrism is an environmental ethic that perceives nature through its functions in fulfilling human needs as individuals and collective society. This ethic is reflected in the attitude of tourists and ecotourism managers who make nature an object that has a value. Therefore, the nature of Bukit Tahura Sultan Adam must be respected and maintained because it has benefits for humans. His love and affection for nature is solely a manifestation of human interests. This research is a critical reflection in increasing care and awareness of protecting the environment in ecotourism areas through a holistic perspective and not sourced from a subordinate view, and not seeing nature only in terms of direct benefits that can be given to humans.